Experimentally enhancing dispersal reveals the outsized importance of transient dynamics in a fluctuating environment - Jessica J. Kowalski; Benjamin Gilbert; Sharon Y. Strauss; Rachel M. Germain (Proceedings of the National Academy of Sciences, 2025)
The size and composition of local species pools are, in part, determined by past dispersal events. Predicting how communities respond to future disturbances, such as fluctuating environmental conditions, requires knowledge of such histories. We assessed the influence of a historical dispersal event on community assembly by simulating various scales of dispersal for 240 serpentine annual plant communities that experienced a large shift from drought to high rainfall conditions over three years. We collected, aggregated, and redistributed the aboveground seed bank (i.e., all loose seed present on the soil surface before the growing season initiates) from 30 sites across five nested spatial scales ( ∼ 1 m, 5 m, 100 m, 5 km, and 10 km), and annually censused communities to identify change in community structure among dispersal scales and over time. Our one-time dispersal manipulation diversified aboveground seed banks, provided insurance against temporal variability at intermediate and large dispersal distances ( ≥ 100 m), and even supported community reassembly toward a new compositional state at the 10 km scale. We also found evidence that temporal lags directed community responses to environmental fluctuations, preventing rare species extirpations and providing subordinate species discrete windows of time to supplement their seed banks. Our results reveal a joint spatiotemporal equilibrium in this system where dispersal through space interacts with temporal fluctuations in climate to support species’ persistence via aboveground seed banks. This experiment underscores the importance of dispersal for diversity maintenance in this global biodiversity hotspot, where the magnitude and frequency of future climate fluctuations is uncertain.